A study companion to Introduction to world religions - Wright, Beth; Partridge, Christopher H. (Christopher Hugh), 1961-; Dowley, Tim (Minneapolis, Fortress Press, 2013)
"The Study Companion is a valuable additional resource for introductory courses in world religions that use Christopher Partridges Introduction to World Religions, Second Edition and can be purchased individually, or as a part of a course pack. Thoroughly checked and updated to work flawlessly with the revised second edition of this important text, the Study Companion provides biographical information, primary source readings, bibliographies, and many other pedagogical tools to enhance the students experience"--Publisher description.
Understanding religion -- Religions of antiquity -- Indigenous religions -- Hinduism -- Buddhism -- Jainism -- Chinese religions -- Korean and Japanese religions -- Judaism -- Christianity -- Islam -- Sikhism -- Religions in today's world.
Includes bibliographical references.
Keywords: Religions -- Introductions; Religions -- Study and teaching